The Relevance of Neutrality in Humanitarian Action in the intra-state Conflicts of the 20th and 21st Century - Holmberg, Daniel H. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Humanitarian Assistance at the Feinstein International Center.; Thesis (M.A.)--Tufts University, 2012.